Deaf School : the Non-Stop Pop Art Punk Rock Party. - Du Noyer, Paul (Liverpool University Press, 2013)
Liverpool's dynamic music scene gave the world The Beatles. What city could hope to follow that? But 12 years later, in 1974, lightning nearly struck twice. Deaf School were a band formed in John Lennon's old art college, rehearsing in the very same rooms. With their chaotic and wildly entertaining brand of rock cabaret, Deaf School were tipped for instant stardom and signed up by Warner Brothers in California. But suddenly, with the world at their feet, Deaf School were swept aside by Britain's punk rock revolution. ""A great band, "" said the Sex Pistols' manager Malcolm McLaren. ""But it's j.